1993
DOI: 10.1091/mbc.4.6.627
|View full text |Cite
|
Sign up to set email alerts
|

Increased LAMP-2 polylactosamine glycosylation is associated with its slower Golgi transit during establishment of a polarized MDCK epithelial monolayer.

Abstract: An endogenous Madin-Darby canine kidney (MDCK) lysosomal membrane glycoprotein that exhibits a basolateral targeting pathway to the lysosome is shown here to exhibit significant N-terminal amino acid sequence identity to lysosomal associated membrane proteins (LAMP-2) of other species. During establishment of the MDCK monolayer after only 1 d of culture, this canine LAMP-2 has a larger molecular size (110 kDa) than following formation of a confluent monolayer after 3 d of culture (100 kDa) due to the increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…All cell culture reagents were obtained from GIBCO͞Life Technologies (Grand Island, NY) unless otherwise indicated. RPE-J cells were maintained in DMEM supplemented with 4% CELLECT Gold FBS (ICN), nonessential amino acids, glutamine, and penicillin͞ streptomycin at 32°C in a 95% air͞5% CO 2 environment as described (21,22). All assays were carried out on cells seeded at a density of 3.5 ϫ 10 5 cells͞cm 2 on Matrigel-coated 1.2-cmdiameter Transwell filters.…”
Section: Methodsmentioning
confidence: 99%
“…All cell culture reagents were obtained from GIBCO͞Life Technologies (Grand Island, NY) unless otherwise indicated. RPE-J cells were maintained in DMEM supplemented with 4% CELLECT Gold FBS (ICN), nonessential amino acids, glutamine, and penicillin͞ streptomycin at 32°C in a 95% air͞5% CO 2 environment as described (21,22). All assays were carried out on cells seeded at a density of 3.5 ϫ 10 5 cells͞cm 2 on Matrigel-coated 1.2-cmdiameter Transwell filters.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed with 3% paraformaldehyde for 15 minutes, washed with PBS supplemented with 0.1 mM Ca 2+ and 1 mM Mg 2+ (PBS-CM) and then incubated for 15 minutes with PBS-CM supplemented with 0.2% BSA to reduce non-specific binding and 0.07% saponin to permeabilize cellular membranes. AC17 anti-LAMP-2 antibody (Nabi et al, 1991;Nabi and Rodriguez-Boulan, 1993) was used to determine the cellular distribution of LAMP-2 using Alexa 488 goat anti-mouse IgG as secondary antibody. Intracellular cholesterol was visualized by filipin labelling (1:25 of a stock solution of 10 mg/ml in DMSO).…”
Section: Immunofluorescencementioning
confidence: 99%
“…After fixation, the cells were rinsed extensively with PBS, pH 7.4, supplemented with 0.1 mM Ca 2ϩ and 1 mM Mg 2ϩ (PBS/CM), and then incubated for 15 min with PBS/CM containing 0.5% BSA at room temperature to reduce nonspecific binding. LAMP-2 distribution was determined using the AC17 anti-LAMP-2 antibody (Nabi et al, 1991;Nabi and Rodriguez-Boulan, 1993) followed by FITC-or Texas Red-conjugated secondary antibodies (Jackson ImmunoResearch, West Grove, PA). Detection of the distribution of L-PHA reactivity was performed using rhodamine-conjugated L-PHA (E-Y Laboratories, San Mateo, CA).…”
mentioning
confidence: 99%
“…Increased expression of polylactosamine and the associated Lewis and blood group antigens are carcinoma markers (Fukuda, 1985;Hakamori, 1989). Modified expression of polylactosamine is also associated with cellular differentiation of various cell types (Spillmann and Finne, 1987;Youakim et al, 1989;Amos and Lotan, 1990;Lee et al, 1990;Tuo et al, 1992;Nabi and Rodriguez-Boulan, 1993). The decreasing polylactosamine glycosylation of the lysosomal LAMP glycoproteins in cultured epithelial cells with time in culture is modulated independently of glycosyltransferase activities (Brockhausen et al, 1991;Nabi and Dennis, 1998), and polylactosamine glycosylation has been shown to be regulated by the Golgi residence time of the protein (Wang et al, 1991;Nabi and Rodriguez-Boulan, 1993;Nabi and Dennis, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation